COVID-19 aus Sicht der Kardiologie - Weckbach, Ludwig T.; Kellnar, Antonia; Stremmel, Christopher; Stark, Konstantin; Kääb, Stefan (DMW - Deutsche Medizinische Wochenschrift, 2020)
The SARS-CoV-2 pandemic has rapidly spread around the world and has led to a substantial morbidity and mortality in many countries. Although Corona Virus Disease 19 (COVID-19) is primarily a respiratory tract infection, there is growing evidence that other organs including the cardiovascular system are affected by COVID-19. In this review, we summarize the association of myocardial injury with in-hospital mortality of COVID-19 patients. Furthermore, we discuss potential mechanisms of myocardial injury including myocarditis and vascular thrombosis. Last, we review the current evidence on drugs which have been evaluated or are currently tested for the treatment of COVID-19 patients.
Keywords: SARS-CoV-2; COVID-19; Myokarditis; thrombotisches Risiko; Remdesivir; Interferon-β